Volatile profile of fermented sausages with commercial probiotic strains and fructooligosaccharides - Bis-Souza, Camila Vespúcio [UNESP]; Pateiro, Mirian; Domínguez, Rubén; Lorenzo, José M.; Penna, Ana Lucia Barretto [UNESP]; da Silva Barretto, Andrea Carla [UNESP] (Springer Nature, 2019)
The effect of the partial substitution of pork back fat by fructooligosaccharides (FOS) and the probiotic strains Lactobacillus paracasei and Lactobacillus rhmanosus on the generation of volatile organic compounds in fermented sausages was investigated. The results obtained showed that these factors significantly affected the total content of organic volatile compounds (7484, 8114, 8372 and 10,737 AU × 104/g for FOS.GG, CON, FOS.BGP1 and FOS samples, respectively). A total of 59 volatile components, mainly hydrocarbons, ketones and esters were isolated. The reduction of fat content by including FOS in the formulation results in positive effects and a greater stability of the volatile profile of the fermented sausages, increasing ester compounds and reducing the undesirable notes of hexanal (probiotic samples showed values < 2 AU × 104/g). Moreover, there was a symbiotic effect when the aforementioned prebiotic fiber was combined with probiotic Lactobacillus strains.
Keywords: Aroma; FOS; Lactic acid bacteria; Meat product; Prebiotic; Volatile compounds